Long-term efficacy of 90Y-DOTATATE in patients with nonresectable pancreatic and small bowel neuroendocrine neoplasms. (August 2016) - Rogowski, Wojciech; Wachuła, Ewa; Lewczuk, Anna; Buscombe, John R; Seklecka, Nina; Sankowski, Artur; Ćwikła, Jarosław B
Aim: To determine the efficacy of 90 Y [DOTA 0, D-Phe 1, Tyr 3 ]-octreotate (DOTATATE) in 67 patients with pancreatic and small bowel neuroendocrine tumors (NETs).Patients & methods: The primary efficacy end point was overall survival (OS) and secondary end points were progression-free survival (PFS) and tumor response.Results: Median PFS in pancreatic and small bowel NETs was 25 and 28 months, respectively, and median OS was 42 and 38.5 months, respectively. No intergroup differences in median OS (p = 0.945) or PFS (p = 0.174) were found, also after adjustment for tumor origin, secretory status and grade, and patient's gender.Conclusion: 90 Y-DOTATATE may have similar efficacy in pancreatic and small bowel NETs. Better WHO performance status at baseline seems to be associated with more favorable outcomes.